Examining the Theme: A Healthy Work Place and its Role in Promoting Work Place Health - Flourish Itulua Abumere (European Scientific Journal, ESJ, 2021)
Workplace health promotion initiatives that aim to improve employees' health and fitness have steadily increased throughout time. Previous studies have looked at the effectiveness, cost-effectiveness, and barriers to participating in workplace health promotion. The number of studies supporting the effectiveness of workplace health promotion in improving employees' health and well-being through changing their health behaviors is rising. This paper focuses on the importance of workplace health promotion in assuring employees' general well-being and the relevance of these perspectives in dealing with workplace illness prevention.